Xanthomonas citri MinC Oscillates from Pole to Pole to Ensure Proper Cell Division and Shape - Lorenzoni, Andre S. G.; Dantas, Giordanni C. [UNESP]; Bergsma, Tessa; Ferreira, Henrique [UNESP]; Scheffers, Dirk-Jan (Frontiers Media Sa, 2017)
Xanthomonas citri (Xac) is the causal agent of citrus canker, a disease that affects citrus crops and causes economic impact worldwide. To further characterize cell division in this plant pathogen, we investigated the role of the protein MinC in cell division, chromosome segregation, and peptidoglycan incorporation by deleting the gene minC using allele exchange. Xac with minC deleted exhibited the classic Amin phenotype observed in other bacteria deleted for min components: minicells and short filamentation. In addition we noticed the formation of branches, which is similar to what was previously described for Escherichia coli deleted for either min or for several low molecular weight penicillin-binding proteins (PBPs). The branching phenotype was medium dependent and probably linked to gluconeogenic growth. We complemented the minC gene by integrating gfp-minC into the amy locus. Xac complemented strains displayed a wild-type phenotype. In addition, GFP-MinC oscillated from pole to pole, similar to MinCD oscillations observed in E coli and more recently in Synechococcus elongatus. Further investigation of the branching phenotype revealed that in branching cells nucleoid organization, divisome formation and peptidoglycan incorporation were disrupted.
Keywords: Xanthomonas citri; MinC; FtsZ; ZapA; ParB; peptidoglycan; citrus canker